SISTEM INFORMASI AKADEMIK SMP 07 KETAPANG BERBASIS WEB - Ibrahim, Aprianda; Widayanti, Rahayu (DINAMIKA DOTCOM, 2013)
Systems and applications can provide an alternative solution for displaying data Academic and introduce it to the public on 07 SMP Ketapang, so that the academic information system will be known by the public. With this application can also be known to any students who have better grades, and students are most undervalued. Academic Information Systems Applications SMP 07 Ketapang-development still needs further development to be used In the maximum..Â Key words: Academic Information System, Web